2018
DOI: 10.1103/physrevb.98.245418
|View full text |Cite
|
Sign up to set email alerts
|

Self-biased current, magnetic interference response, and superconducting vortices in tilted Weyl semimetals with disorder

Abstract: We have generalized a quasiclassical model for Weyl semimetals with a tilted band in the presence of an externally applied magnetic field. This model is applicable to ballistic, moderately disordered, and samples containing a high density of nonmagnetic impurities. We employ this formalism and show that a self-biased supercurrent, creating a ϕ 0 -junction, can flow through a triplet channel in Weyl semimetals. Furthermore, our results demonstrate that multiple supercurrent reversals are accessible through vary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 87 publications
4
23
0
Order By: Relevance
“…By introducing a z-component to the inversion symmetry breaking term, the current-phase-relation undergoes a phase shift leading to a nonvanishing current at ϕ = 0, π, creating a ϕ 0 -state. Our results are consistent with recent findings in quasiclassical Weyl semimetal systems containing disorder 8 . Within a quasiclassical approach, it was found that supercurrent can flow through a triplet channel, and the ϕ 0 state is independent of the diffusion constant, demonstrating that this self-biased current can occur regardless of the density of nonmagnetic impurities and disorder in WS systems.…”
Section: B Charge Supercurrentsupporting
confidence: 93%
See 2 more Smart Citations
“…By introducing a z-component to the inversion symmetry breaking term, the current-phase-relation undergoes a phase shift leading to a nonvanishing current at ϕ = 0, π, creating a ϕ 0 -state. Our results are consistent with recent findings in quasiclassical Weyl semimetal systems containing disorder 8 . Within a quasiclassical approach, it was found that supercurrent can flow through a triplet channel, and the ϕ 0 state is independent of the diffusion constant, demonstrating that this self-biased current can occur regardless of the density of nonmagnetic impurities and disorder in WS systems.…”
Section: B Charge Supercurrentsupporting
confidence: 93%
“…Hence, the predicted robust self-biased current should be experimentally accessible over a wide range of parameters. 8,9,[76][77][78][79] It is worth men- tioning that in a recent experiment, 79 this self-biased current was observed using a Bi 2 Se 3 platform, which is in agreement with theoretical predictions for topological insulator Josephson junctions [76][77][78] .…”
Section: B Charge Supercurrentsupporting
confidence: 81%
See 1 more Smart Citation
“…[67][68][69][70]. This method agrees well with Gorkov's Green's function approach and also can provide access to the quasiclassical regime where the Fermi energy is the largest energy in the system [67][68][69][70][71][72][73]. To simplify the calculations, we have ignored the inverse proximity effects and considered a situation where the roughness of the interfaces plays a relatively weak role, which is the experimentally relevant regime [1,2].…”
supporting
confidence: 54%
“…The behavior of the supercurrent is governed by the complicated interplay of lattice symmetry and the actual pairing mechanism. If unconventional odd-parity p-wave and f -wave pairing mechanisms are involved, the combination of an appropriate Zeeman field in a Josephson junction with different p-wave ( f -wave) orientations in superconducting leads (or s-wave electrodes) can result in a self-biased current [67][68][69][70][71][72][73]. The cases considered above do not exhaust all theoretical possibilities for introducing superconductivity in the BLG system, but they serve as illustrative examples for what can take place, while further computations should be guided by experimental systems.…”
mentioning
confidence: 99%